2008
DOI: 10.1093/mutage/gen029
|View full text |Cite
|
Sign up to set email alerts
|

The bile acid deoxycholic acid has a non-linear dose response for DNA damage and possibly NF- B activation in oesophageal cells, with a mechanism of action involving ROS

Abstract: Deoxycholic acid (DCA) is a secondary bile acid implicated in various cancers of the gastrointestinal (GI) tract. In oesophageal adenocarcinoma, DCA is believed to contribute to carcinogenesis during reflux where stomach contents enter the lower oesophagus. It is imperative that we understand the mechanisms whereby oesophageal carcinogens function in order that therapeutic options may be developed. We have previously shown that DCA can damage chromosomes and does so through its generation of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 28 publications
1
61
0
1
Order By: Relevance
“…In BO and OAC cell lines, bile acids induce increased ROS and increased cell proliferation in a complex system, possibly by induction of PI-PLCγ2, ERK2 MAP kinase, and NADPH oxidase NOX5-S via the TGR5 receptor [80,81]. Similar to findings in the colon, antioxidants such as reservatrol and vitamin C can block DCA-induced NF-κB expression [75], while people with high antioxidant intake have a 50% decreased risk of developing OAC compared with those with a low intake [82].…”
Section: Role Of Hypoxia and Oxidative Stressmentioning
confidence: 52%
See 1 more Smart Citation
“…In BO and OAC cell lines, bile acids induce increased ROS and increased cell proliferation in a complex system, possibly by induction of PI-PLCγ2, ERK2 MAP kinase, and NADPH oxidase NOX5-S via the TGR5 receptor [80,81]. Similar to findings in the colon, antioxidants such as reservatrol and vitamin C can block DCA-induced NF-κB expression [75], while people with high antioxidant intake have a 50% decreased risk of developing OAC compared with those with a low intake [82].…”
Section: Role Of Hypoxia and Oxidative Stressmentioning
confidence: 52%
“…In Barrett's tissue, dysplasia is associated with increased oxidative DNA damage [72]. Bile acids can induce DNA damage via ROS production [73] and NF-κB activation [74][75][76] (another link to the inflammatory process), with increases in DNA double-strand breaks and intracellular ROS levels [77,78]. NO can increase invasiveness of dysplastic and cancerous cells via regulation of MMPs and TIMPs [79].…”
Section: Role Of Hypoxia and Oxidative Stressmentioning
confidence: 99%
“…Colonic mucosal proliferation has been associated positively with secondary bile acid levels [94]. In vitro studies have demonstrated the ability of secondary bile acids to up regulate NF-κβ expression and induce DNA damage through the generation of reactive oxygen species [95]. Bile salt hydrolases (BSHs) are crucial for bile acid modification by the gut microbiota.…”
Section: Evidence For Correlations Of Microbiota With Crcmentioning
confidence: 99%
“…Bile acids have been shown to be damaging to esophageal epithelial cells by affecting membrane permeability, cell proliferation and differentiation, increasing free radicals, inducing DNA damage and up-regulating oncogenes [11,[14][15][16][17][18][19][20]. More specifically, both gastric acid and bile acids have been shown to activate NF-kappa B, a major molecule that is up-regulated in and intrinsic to cancer development.…”
Section: Hpimentioning
confidence: 99%